Design, synthesis, and antihypertensive activity of curcumin-inspired compounds via ACE inhibition and vasodilation, along with a bioavailability study for possible benefit in cardiovascular diseases - Zhuang XD; Liao LZ; Dong XB; Hu X; Guo Y; Du ZM; Liao XX; Wang LC (Dove Medical Press, 2016)
Xiao-dong Zhuang,1,* Li-zhen Liao,2,* Xiao-bian Dong,1 Xun Hu,1 Yue Guo,1 Zhi-min Du,1 Xin-xue Liao,1 Li-chun Wang1 1Department of Cardiology, First Affiliated Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Department of Health, Guangdong Pharmaceutical University, Guangzhou Higher Education Mega Center, Guangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: This study describes the synthesis of a novel series of curcumin-inspired compounds via a facile synthetic route. The structures of these derivatives were ascertained using various spectroscopic and analytic techniques. The pharmacological effects of the target analogs were assessed by assaying their inhibition of angiotensin-converting enzyme (ACE). All of the synthesized derivatives exhibited considerable inhibition of ACE, with half-maximal inhibitory concentrations ranging from 1.23 to 120.32 µM. In a docking analysis with testicular ACE (tACE), the most promising inhibitor (4j) was efficiently accommodated in the deep cleft of the protein cavity, making close interatomic contacts with Glu162, His353, and Ala356, comparable with lisinopril. Compounds 4i, 4j, 4k, and 4l were further selected for determination of their vasodilator activity (cardiac output and stroke volume) on isolated rat hearts using the Langendorff technique. The bioavailability of compound 4j was determined in experimental mice. Keywords: curcumin, synthesis, ACE inhibition, antihypertensive, vasodilation, bioavailability